Conceptual art - Godfrey, Tony 1951- (Phaidon Press, 1998)
What is art? Must it be a unique, saleable luxury item? Can it be a concept that never takes material form? Or an idea for a work that can be repeated endlessly? Conceptual art favours an engagement with such questions. As the variety of illustrations in this book shows, it can take many forms: photographs, videos, posters, billboards, charts, plans and, especially, language itself. Tony Godfrey has written a clear, lively and informative account of this fascinating phenomenon. He traces the origins of Conceptual art to Marcel Duchamp and the anti-art gestures of Dada, and then establishes links to those artists who emerged in the 1960s and early 1970s, whose work forms the heart of this study: Joseph Kosuth, Lawrence Weiner, Victor Burgin, Marcel Broodthaers and many others.
Keywords: Geschichte 1900-2000; Geschichte 1910-1997; Art - 20e siècle; Art conceptuel; Conceptuele kunst; Kunst; Art, Modern -- 20th century; Conceptual art; Concept-art